Proteomic analysis of the urine of Dirofilaria immitis infected dogs - Hormaeche, Marta; Carretón Gomez, Elena; González-Miguel, Javier; Gussoni, Stefania; Montoya Alonso, José Alberto; Simón Martín,Fernando; Morchon Garcia,Rodrigo (Veterinary Parasitology, 2014)
Canine cardiopulmonary dirofilariosis caused by Dirofilaria immitis habitually develops as a chronic disease affecting pulmonary arteries, lung parenchyma and heart. Other organs like kidneys can also be involved. Renal pathology is a consequence of glomerulonephritis whose main sign is proteinuria. The aim of the present work is to identify proteins excreted in the urine of D. immitis infected dogs showing proteinuria, and the possible contribution of their loss to heartworm disease. Proteinuria is higher in microfilaremic (mf+) than in amicrofilaremic (mf−) dogs. Using bidimensional electrophoresis and mass spectrometry 9 different proteins from Canis lupus familiaris in the urine of both mf− and mf+ dogs were identified (serotransferrin isoform 6, serum albumin precursor, albumin, immunoglobulin gamma heavy chain D, apolipoprotein A-I, immunoglobulin lambda-like polypeptide 5-like, arginine esterase precursor, inmunoglobulin gamma heavy chain B and hemoglobin subunit alpha). Furthermore, 3 additional proteins were identified only in the urine of mf+ dogs, corresponding to dog fibrinogen alpha chain and immunoglobulin gamma heavy chain A and actin 2 homologous to a protein of Brugia malayi. The loss of these proteins and other in the urine of D. immitis infected dogs could affect the general condition of parasitized dogs through the interference in the cholesterol metabolism and O2 transport, among other mechanisms.